Chilling and cooking rate effects on some myofibrillar determinants of tenderness of beef - King, D.A.; Dikeman, Michael E.; Wheeler, T.L.; Kastner, Curtis L.; Koohmaraie, M. (American Society of Animal Science, 2008)
Our objectives were to examine the effects of prerigor excision and rapid chilling vs. conventional carcass chilling of two muscles on proteolysis and tenderness during the postmortem storage, as well as the effects of fast and slow rates of cooking on myofibrillar characteristics and tenderness. The longissimus thoracis (LT) and triceps brachii (TB), long head muscles were removed 45 min after exsanguination from the left side of 12 carcasses and chilled in an ice bath to induce cold shortening (excised, rapidly chilled). At 24 h postmortem, the corresponding muscles were removed from the right side (conventionally chilled). All muscles were cut into 2.54-cm-thick steaks and assigned to one of two postmortem times (1 or 14 d), and to raw and cooking treatments. Steaks were cooked at 260°C(FAST) or 93°C(SLOW) in a forced-air convection oven to an internal temperature of 70°C. Cooking loss, cooking time, and Warner-Bratzler shear force (WBSF) were measured on cooked steaks. Sarcomere length (SL) and the extent of proteolysis of desmin were measured on raw and cooked steaks. As expected, the excised, rapidly chilled muscles had a much more rapid (P < 0.05) temperature decline than those that were conventionally chilled. The excised, rapidly chilled treatment resulted in shorter (P < 0.05) SL, and SL was shorter (P < 0.05) in LT than in TB steaks. Raw steaks had longer (P < 0.05) SL than cooked steaks, regardless of chilling treatment. The FAST cooking resulted in shorter (P < 0.05) SL thanSLOWcooking in conventionally chilled steaks, but cooking rate had no effect (P > 0.05) on SL of rapidly chilled steaks. Generally, TB steaks required longer (P < 0.05) cooking times and had higher (P < 0.05) cooking losses than LT steaks, and FAST-cooked steaks had greater (P < 0.05) cooking losses than SLOW-cooked steaks. Rapidly chilled steaks had less (P < 0.05) degradation of desmin than conventionally chilled steaks (31 vs. 41%). Aging for 14 d increased (P < 0.05) desmin degradation. Rapid chilling of muscles resulted in much higher (P < 0.05) WBSF values, whereas aging resulted in lower (P < 0.05) WBSF values. The SLOW-cooked TB steaks were more tender (P < 0.05) than FAST-cooked TB steaks and LT steaks cooked at either rate. Excised, rapidly chilled muscles underwent proteolysis, but it occurred at a slower rate during the first 24 h postmortem than it did in conventionally chilled muscles. Cooking rate did not affect tenderness of LT steaks, but SLOW cooking resulted in more tender TB steaks.
Keywords: Food science; Beef; Chilling; Cooking; Proteolysis; Tenderness; Rate